2013
DOI: 10.1038/cr.2013.143
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the selective and ABA-independent inhibition of PP2CA by PYL13

Abstract: PYR1/PYL/RCAR family proteins (PYLs) are well-characterized abscisic acid (ABA) receptors. Among the 14 PYL members in Arabidopsis thaliana, PYL13 is ABA irresponsive and its function has remained elusive. Here, we show that PYL13 selectively inhibits the phosphatase activity of PP2CA independent of ABA. The crystal structure of PYL13-PP2CA complex, which was determined at 2.4 Å resolution, elucidates the molecular basis for the specific recognition between PP2CA and PYL13. In addition to the canonical interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 34 publications
(64 reference statements)
0
82
1
1
Order By: Relevance
“…In two recent studies, RCAR7 has been claimed to selectively inhibit PP2CA independent of ABA and not to bind ABA because of changes in conserved amino acid residues involved in ABA binding (41,42). We found no evidence for this claim.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…In two recent studies, RCAR7 has been claimed to selectively inhibit PP2CA independent of ABA and not to bind ABA because of changes in conserved amino acid residues involved in ABA binding (41,42). We found no evidence for this claim.…”
Section: Resultscontrasting
confidence: 55%
“…S2). Q38 of RCAR7 has been postulated to disrupt coordination of the carboxyl group of ABA mediated by a conserved lysine residue in other RCARs, and the bulky phenylalanine residue of RCAR7 at position 71 might generate a "steric clash" with the methyl group of ABA (41). RCAR7 Q38L , RCAR7…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstitution assays in Arabidopsis protoplasts showed that all PYL members except for PYL13, which is ABA-insensitive [110] and was therefore not tested, are able to activate ABA-induced gene expression [100] , suggesting functional overlap between the PYL members. In line with this notion, multiple mutations, such as pyr1pyl1pyl2pyl4 quadruple mutations [6] and pyr1pyl1pyl2pyl4pyl5pyl8 sextuple mutations [117] , are required to generate robust ABA-insensitive [117] .…”
Section: Transmitting the Aba Signal To Pp2csmentioning
confidence: 99%
“…The earliest PYL structural studies were based on PYR1, PYL1, and PYL2 [102][103][104][105][106] . To date, the structures of PYL3, PYL5, PYL9, PYL10, and PYL13 have also been solved, either in their apo or ligand-bound forms or in complexes with PP2C [107][108][109][110] . The currently available PYL structures represent more than half of the 14-member family of PYL proteins in Arabidopsis, and all of them exhibit the helix-grip fold, a hallmark of START domain/Bet v 1-fold proteins, which is characterized by a long C-terminal α-helix surrounded by a curved anti-parallel β-sheet and several smaller α-helices.…”
Section: Structural Elucidation Of the Early Aba Signaling Mechanismsmentioning
confidence: 99%